2022
DOI: 10.1021/acscatal.2c00389
|View full text |Cite
|
Sign up to set email alerts
|

Proton Donors Induce a Differential Transport Effect for Selectivity toward Ammonia in Lithium-Mediated Nitrogen Reduction

Abstract: Alternative approaches for producing ammonia are necessary to reduce the environmental impact of its production. The lithium-mediated electrochemical nitrogen reduction reaction (LM-NRR) is one attractive alternative method for producing ammonia at small scales in a distributed process. This process requires a proton donor in the electrolyte to produce ammonia from nitrogen, but the role of the proton donor in selective ammonia production is not well understood. In this work, we experimentally tested several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 43 publications
6
112
3
Order By: Relevance
“…Although the model SLDs for the single layer were consistent between electrolyte conditions, the modeled layer thicknesses began to exhibit differences after t = 240 s, with the layer in the 0 M-EtOH electrolyte becoming thicker than that in the 0.17 M-EtOH electrolyte. This indicates that, although the presence of EtOH does not appear to detectably affect the composition of the layer that forms during the initial stages of chronopotentiometry, EtOH may, as expected, cause decomposition of some portion of the layer via the ethanolysis of Li 3 N and prevent it from growing as quickly as the layer without EtOH. , This is consistent with recent work that suggests that the presence of a proton donor increases the permeability of the formed SEI at the electrode surface, improving diffusion of nitrogen and the proton donor to the electrode surface, and prevents side reactions of Li with the electrolyte to increase ammonia production …”
Section: Time-resolved Measurementsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the model SLDs for the single layer were consistent between electrolyte conditions, the modeled layer thicknesses began to exhibit differences after t = 240 s, with the layer in the 0 M-EtOH electrolyte becoming thicker than that in the 0.17 M-EtOH electrolyte. This indicates that, although the presence of EtOH does not appear to detectably affect the composition of the layer that forms during the initial stages of chronopotentiometry, EtOH may, as expected, cause decomposition of some portion of the layer via the ethanolysis of Li 3 N and prevent it from growing as quickly as the layer without EtOH. , This is consistent with recent work that suggests that the presence of a proton donor increases the permeability of the formed SEI at the electrode surface, improving diffusion of nitrogen and the proton donor to the electrode surface, and prevents side reactions of Li with the electrolyte to increase ammonia production …”
Section: Time-resolved Measurementsupporting
confidence: 90%
“…13,40 This is consistent with recent work that suggests that the presence of a proton donor increases the permeability of the formed SEI at the electrode surface, improving diffusion of nitrogen and the proton donor to the electrode surface, and prevents side reactions of Li with the electrolyte to increase ammonia production. 55 Thus, using neutron reflectometry, we have demonstrated that, following chronopotentiometry for 30 min, a diffuse SEI layer remains; the neutron reflectometry data, in tandem with previous reports, suggest that this layer may consist predominantly of carbonaceous electrolyte degradation products at the electrode surface. Time-resolved neutron reflectometry measurements support a model of the electrode−electrolyte interface in which, during the initial states of NRR, a single, Li-containing layer forms atop the Mo electrode, with no separate carbonaceous SEI layer observed during the first 6 min of chronopotentiometry.…”
Section: ■ Initial State At Ocpsupporting
confidence: 82%
“…The reduction in RCT with LiClO4 concentration, as shown in Figure 5 and Table S3, may suggest an increase in proton mobility through the SEI with increased salt concentration. However, the increasing thickness, and perhaps density, may also inhibit the transfer of reactants to the catalytically active surface 44 . It may be that the combination of these factors also results in the suppression of Faradaic efficiency at higher LiClO4 concentrations.…”
Section: Section 4: Sei Characterisationmentioning
confidence: 99%
“…Transition metal-based catalysts have drawn much attention as they can weaken NN bonds and strengthen metal–nitrogen bonding through σ donation and π backdonation between transition metals and N 2 . , However, the electrocatalytic activity and selectivity are still far from satisfactory because most transition metal-based catalysts favor competitive adsorption of H + over N 2 . , Recent breakthroughs have been made on suppressing the parasitic hydrogen evolution reaction (HER), such as interface engineering, nonaqueous electrolyte regulation, and cation incorporation . Nevertheless, protons participate in steps of proton-coupled electron transfer (PCET) in NRR, and the inhibition of proton transfer will inevitably limit the activation of N 2 molecules . Hence, it is desirable to develop novel electrocatalysts with balanced thermodynamics and kinetics to promote nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Nevertheless, protons participate in steps of proton-coupled electron transfer (PCET) in NRR, 13 and the inhibition of proton transfer will inevitably limit the activation of N 2 molecules. 14 Hence, it is desirable to develop novel electrocatalysts with balanced thermodynamics and kinetics to promote nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%